2017
DOI: 10.1002/jcu.22462
|View full text |Cite
|
Sign up to set email alerts
|

Successful ultrasound‐guided percutaneous embolization of renal pseudoaneurysm by autologous blood clot: Preliminary report of a new method

Abstract: We report the case of a 25-year-old female with renal arteriovenous fistula and pseudoaneurysm (PA) formation following renal core-needle biopsy, treated successfully by ultrasound-guided percutaneous embolization with autologous blood clot injection. After inserting a 15-gauge needle within the PA sac, 10 ml of blood was retrieved from the sac, and then reinjected into the PA as well as in the needle tract after the obtained blood completely clotted. The procedure was completed by manual compression of the fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…They performed an ultrasoundguided percutaneous injection of ABC and successfully embolised that. 16 Our research did not find any study about the use of autologous clot embolisation in the treatment of femoral pseudoaneurysm. The main reason for choosing this method in our patient was the fear of the allergic side effects of injecting a large volume of embolisation agents such as thrombin and its re-entry into the patient's bloodstream due to the short neck of PA.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…They performed an ultrasoundguided percutaneous injection of ABC and successfully embolised that. 16 Our research did not find any study about the use of autologous clot embolisation in the treatment of femoral pseudoaneurysm. The main reason for choosing this method in our patient was the fear of the allergic side effects of injecting a large volume of embolisation agents such as thrombin and its re-entry into the patient's bloodstream due to the short neck of PA.…”
Section: Discussionmentioning
confidence: 72%
“…5 Today, many studies have reported the injection of an autologous blood clot (ABC) as an efficient embolising agent due to lower cost, simple usage, and no allergic reaction. 15,16 This method is now being used for the treatment of organ hemorrhage due to trauma and non-ischemic, high-flow priapism. 10,15,17 Emin Ozbek et al reported a case of proximal partial priapism which was treated successfully with ABC embolisation 15 Guliz Yilmaz et al reported a case of painless priapism due to PA and fistula of the left cavernosal artery as result of a trauma, which fully recovered by trans-arterial embolisation of ABC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This justifies why these patients do not benefit from anti-acid therapy [ 24 ], and in our study, this is proven. Moreover, different studies on various subjects have published the regarding the above results [ 25 ] [ 26 ] [ 27 ] [ 28 ] [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the help of the beveled-tip needle, percutaneous interventions and therapies have been widely involved in current clinical procedures, such as brachytherapy [1,2], tissue biopsy [3,4], and drug delivery [5,6]. In intervention procedures, less needle misplacement will lead to a more reliable treatment and a more accurate medical practice.…”
Section: Introductionmentioning
confidence: 99%